PENGARUH STRES KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT.ACCENTUATES CABANG KOTA BENGKULU (Studi Kasus Karyawan Sales Counter) - Ichsan Gustianto; Islamuddin Islamuddin (UM. Bengkulu, 2022)
Abstract : This study aims to determine the effect of work stress and compensation on employee performance at PT. Accentuates Bengkulu City Branch. Theresearch type used was the quantitative method. The object of the research was the employees of PT.Accentuates Bengkulu City Branch using the sampling method namely the total sampling technique. The respondents consisted of 42 people. The researcher used the data collection methods by means of observation, interviews and distributing questionnaires. The data was analyzed using Instrument Tests. They were Validity Test and Reliability Test, Classical Assumption Test namely Multicollinearity Test, Normality Test and Heteroscedasticity Test, Multiple Linear Regression Analysis Test, Coefficient of Determination (R2), and Hypothesis Testing namely t-test and f-test. The results show that the work stress variable has a negative and partially significant effect on the employee performance at PT. Accentuates Bengkulu City Branch. The compensation variable has a positive and partially significant effect on the employee performance at PT. Accentuates Bengkulu City Branch, while the work stress and compensation have a significant effect simultaneously on the Employee Performance PT.Accentuates Bengkulu City Branch. Keywords: Job Stress, Compensation, Employee Performance